Doped aluminum lithium adsorption material as well as preparation method and application thereof

By introducing transition metals and non-metallic elements into aluminum-based lithium adsorbents, doping materials are formed, and granulation technology, the problem of low environmental pollution and adsorption capacity of lithium adsorbents when desorbing lithium is solved, achieving low Dissolution loss, high adsorption performance and structural stability are suitable for the extraction process of lithium.

CN119258976APending Publication Date: 2025-01-07QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411412174.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing lithium adsorbents require strong acids or strong alkalis when desorbing lithium, resulting in increased costs and environmental pollution. At the same time, aluminum-based lithium adsorbents have problems with low adsorption capacity and large aluminum dissolution loss, and it is necessary to develop low dissolution loss and high adsorption properties. adsorbent.

Method used

Using doped aluminum lithium adsorption materials, the interlayer spacing and surface charge are adjusted to improve lithium by introducing transition metal elements and non-metal elements such as Co, Mn, Zn, Cu, F, P, S in LiAl-LDHs. Adsorption capacity and structural stability, and the lithium adsorbent is formed by mixing with polyvinyl chloride and polyacrylonitrile to enhance its stability.

Benefits of technology

Low aluminum dissolution loss, high lithium adsorption capacity and structural stability are achieved, cost reduction, improved cycle stability performance, and significantly improved Al dissolution loss and structural stability in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258976A_ABST
    Figure CN119258976A_ABST
Patent Text Reader

Abstract

The invention provides a doped aluminum lithium adsorption material as well as a preparation method and application thereof. The doping type aluminum lithium adsorption material comprises LiAl-LDHs and doping elements, the doping elements comprise transition metal elements and / or non-metal elements, the transition metal elements comprise one or more of Co, Mn, Zr, Zn, Cu and Ni, and the non-metal elements comprise one or more of F, P, S and Se; the molar ratio of Li to Al contained in the doped aluminum lithium adsorption material is (0.5-5): 1, and the molar concentration of the contained doped element is 0.1-10% of the molar concentration of the contained Al. The doped aluminum lithium adsorption material provided by the invention has relatively low aluminum dissolution loss, relatively high lithium adsorption capacity and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum-based lithium adsorption materials, and specifically relates to a doped aluminum-based lithium adsorption material and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, lithium plays an important role in all walks of life, especially in the production of rechargeable batteries for electronic devices, electric vehicles and energy storage systems. Lithium can also be used in the pharmaceutical, ceramic, glass and aerospace fields. Its light weight and high energy density make it an important element to promote technological progress and sustainable development. In recent years, with the needs of economy and life, the demand for lithium resources has continued to increase. Therefore, how to mine lithium resources more efficiently and environmentally friendly has become particularly important. Compared with extracting lithium resources from solid ores, extracting lithium from salt lake brine is cheaper, less energy consuming and more environmentally friendly.

[0003] At present, the methods for extracting lithium from salt lake brine include membrane method, chemical precipitation method, solvent extraction method, crystallization method, flotation method, adsorption method and the electrochemical separation technology that has attracted much attention. The adsorption method has the advantages of low cost and low energy consumption. However, with the sharp decline in the price of Li2CO3, it is even more necessary to continue to develop higher performance and lower cost lithium adsorbents to reduce costs and improve efficiency. At present, the adsorbents used mainly include manganese / titanium-based lithium adsorbents, aluminum-based lithium adsorbents and organic-based lithium adsorbents. The common problem of manganese / titanium-based lithium adsorbents for desorption of lithium is that strong acid is required for desorption, while lithium adsorption requires a solution environment of pH>10. The use of a large amount of acid and alkali will lead to increased costs and environmental pollution, so it is not suitable for use in the weak ecological environment of the plateau. Aluminum-based lithium adsorbents (Li / Al-LDHs) are layered crystals composed of oxygen-coordinated octahedral stacks. Hydroxyl groups exist at the six vertices of the octahedron. Water molecules and anions are inserted between the lithium layer and the aluminum layer to form precursors for lithium extraction. The active vacancies left after lithium ions are deintercalated in the layered structure can selectively adsorb Li in brine. + . Aluminum-based lithium adsorbents do not require acid or alkali during adsorption and desorption. When desorbing lithium, only deionized water is needed, which is both environmentally friendly and low-cost, and has broad development prospects. However, aluminum-based lithium adsorbents have the problem of low adsorption capacity. At the same time, long-term insertion and removal of lithium will lead to serious loss of Al, and there is a problem of large Al dissolution loss. Therefore, it is necessary to continue to develop adsorbents with low dissolution loss and high adsorption performance. Summary of the invention

[0004] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0005] One of the purposes of the present invention is to provide a doped aluminum-based lithium adsorption material, the doped aluminum-based lithium adsorption material comprises LiAl-LDHs and a doping element, the doping element comprises a transition metal element and / or a non-metallic element, the transition metal element comprises one or more of Co, Mn, Zr, Zn, Cu, and Ni, and the non-metallic element comprises one or more of F, P, S, and Se;

[0006] The molar ratio of Li to Al in the doped aluminum-based lithium adsorption material is 0.5-5:1, and the molar concentration of the doping element is 0.1-10% of the molar concentration of the Al.

[0007] The doped aluminum-based lithium adsorption material provided by the present invention has lower aluminum dissolution loss, higher lithium adsorption capacity and structural stability.

[0008] In some preferred embodiments, the doped aluminum-based adsorbent material includes a transition metal element and a non-metal element, the transition metal element includes Co, and the non-metal element includes F, that is, the doped aluminum-based adsorbent material is Co and F co-doped LiAl-LDHs; or, the transition metal element includes Cu, and the non-metal element includes S, that is, the doped aluminum-based adsorbent material is Cu and S doped LiAl-LDHs; or, the transition metal element includes Zn, and the non-metal element includes F, that is, the doped aluminum-based adsorbent material is Zn and F doped LiAl-LDHs. The present invention finds that the aluminum-based adsorbent material co-doped with the above-mentioned transition metal elements and non-metal elements can not only synergistically improve the adsorption capacity but also further reduce aluminum dissolution loss and improve structural stability, showing more excellent cyclic stable use performance of efficient adsorption.

[0009] More preferably, the transition metal element includes Co and the non-metal element includes F; or the transition metal element includes Cu and the non-metal element includes S. The adsorption performance and structural stability of the aluminum-based adsorption material formed by these two doping schemes can be further improved.

[0010] In the embodiment where the doped aluminum-based adsorption material includes transition metal elements and non-metal elements, the molar ratio of the transition metal elements to the non-metal elements is 0.01-5:0.01-5, for example, 0.01-5:1, 0.1-5:1, 1-5:1.

[0011] The second object of the present invention is to provide a method for preparing a doped aluminum-based adsorption material, comprising: subjecting a mixed reaction system containing a lithium source, an aluminum source, urea, a doping element precursor and a solvent to a hydrothermal reaction at a temperature of 100-180° C. for 2-12 hours to obtain a doped aluminum-based lithium adsorption material;

[0012] Alternatively, a mixed solution containing an aluminum source, a doping element precursor and a solvent is provided, and the pH value of the mixed solution is adjusted to 8 to 10; a lithium source is added to the mixed solution in batches to obtain a mixed reaction system, and stirring is maintained at a temperature of 20 to 80° C. for 2 to 8 hours to obtain a doped aluminum-based lithium adsorption material;

[0013] Among them, the doping element precursor is used to provide transition metal elements and / or non-metal elements, the transition metal elements include one or more of Co, Mn, Zr, Zn, Cu, and Ni, and the non-metal elements include one or more of F, P, S, and Se.

[0014] In some embodiments, the solvent in the mixed reaction system includes water.

[0015] In some embodiments, the amounts of lithium source, aluminum source and doping element precursor in the mixed reaction system satisfy: the molar ratio of Li to Al contained in the doped aluminum-based lithium adsorption material is 0.5-5:1, and the molar concentration of the doping element contained is 0.1-10% of the molar concentration of Al contained.

[0016] In some embodiments, the doping element precursor can provide transition metal elements and non-metal elements, and the amount of the doping element precursor is such that the molar ratio of transition metal elements and non-metal elements in the prepared doped aluminum-based lithium adsorption material is 0.01-5:0.01-5.

[0017] In some embodiments, the doping element precursor includes a Co precursor and a F precursor; or, the doping element precursor includes a Cu precursor and a S precursor; or, the doping element precursor includes a Zn precursor and a F precursor.

[0018] In some embodiments, the molar concentration of urea in the mixed reaction system is 0.5-2 times the molar concentration of aluminum.

[0019] In some embodiments, the lithium source includes one or more of lithium chloride, lithium sulfate or lithium nitrate, but is not limited thereto.

[0020] In some embodiments, the aluminum source includes one or more of aluminum chloride, aluminum sulfate, or aluminum nitrate, but is not limited thereto.

[0021] In some embodiments, the precursor providing the transition metal element includes one or more of soluble chlorides, nitrates, sulfates or carbonates of the transition metal element, but is not limited thereto.

[0022] In some embodiments, the precursor providing F includes one or more of LiF, NaF, and KF; the precursor providing P includes one or more of phosphoric acid, Na3PO4, K3PO4, Ca3(PO4)2, Na4P2O7, and NaH2PO2; the precursor providing S includes soluble sulfides and / or soluble sulfates, and the soluble sulfides include Al2S3; the precursor providing Se includes one or more of Na2SeO3, H2SeO3, K2SeO3, H2SeO4, K2SeO4, and Na2SeO4.

[0023] The third object of the present invention is to provide a doped aluminum-based lithium adsorption material, characterized in that it is prepared by the method described in any of the above technical solutions.

[0024] The fourth object of the present invention is to provide a lithium adsorbent, the raw materials of the lithium adsorbent comprising the doped aluminum-based lithium adsorbent material described in any one of the above technical solutions, polyvinyl chloride (PVC), polyacrylonitrile (PAN) and a cross-linking agent, the ratio of the mass of the doped aluminum-based lithium adsorbent material to the total mass of polyvinyl chloride and polyacrylonitrile is 3:1-5:1, the mass ratio of polyvinyl chloride to polyacrylonitrile is 0.2:0.8-0.8:0.2, and the concentration of the cross-linking agent is 0.05-10wt% of the total mass of the doped aluminum-based lithium adsorbent material, polyvinyl chloride and polyacrylonitrile.

[0025] In some embodiments, the cross-linking agent includes one or a combination of ethylenediamine, a silane coupling agent, and polyethylene glycol diacrylate.

[0026] A fifth object of the present invention is to provide a method for preparing the lithium adsorbent, comprising:

[0027] Providing the doped aluminum-based lithium adsorption material;

[0028] At least the doped aluminum-based lithium adsorbent material, polyvinyl chloride, polyacrylonitrile and a crosslinking agent are uniformly dispersed in a polar aprotic solvent to obtain a mixture;

[0029] The mixture is injected into water to solidify the mixture in the water, and a solidified product is obtained after solid-liquid separation, which is a granulated lithium adsorbent.

[0030] In the lithium adsorbent provided by the present invention, PVC and PAN are used as granulating agents and are mixed with the doped aluminum-based lithium adsorbent material for granulation, wherein the cross-linking agent can cross-link with -CN on PAN and -OH on PVC to form a network structure, and increase the hydrophilicity and the channel for ion transmission, so that the prepared lithium adsorbent has good adsorption performance and stability; compared with the ungranulated doped aluminum-based lithium adsorbent material, the dissolution loss problem of the lithium adsorbent formed by granulation is further improved, and the practical application and stability performance are also improved.

[0031] In some embodiments, the polar aprotic solvent includes dimethylformamide and / or N-methylpyrrolidone.

[0032] The sixth object of the present invention is to provide the use of the doped aluminum-based lithium adsorption material or the lithium adsorbent in lithium extraction from brine or seawater.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] (1) The doped aluminum-based lithium adsorption material provided by the present invention changes the interlayer spacing and surface charge of LiAl-LDHs by doping, thereby improving the lithium adsorption capacity and structural stability of the lithium adsorption material, and the doped aluminum-based lithium adsorption material also exhibits lower aluminum dissolution loss;

[0035] (2) The present invention adopts doped aluminum-based lithium adsorbent material, PVC, PAN and a cross-linking agent for mixed granulation to form a lithium adsorbent. Compared with the ungranulated doped aluminum-based lithium adsorbent material, the granulated lithium adsorbent maintains good adsorption performance, and the Al dissolution and structural stability are further improved, which is beneficial to its applicability in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 Electron microscopy image of Co-Li / Al-LDHs prepared in Example 4 of the present invention;

[0038] Figure 2 It is the XRD diagram of the lithium adsorbent prepared in Examples 4-8 and Comparative Example 1 of the present invention;

[0039] Figure 3It is a partial enlarged XRD diagram of the lithium adsorbent prepared in Examples 4-8 and Comparative Example 1 of the present invention;

[0040] Figure 4 It is the infrared spectra of the lithium adsorbents prepared in Examples 4-8 and Comparative Example 1 of the present invention;

[0041] Figure 5 is a Raman spectrum of Co-Li / Al-LDH of Example 4 of the present invention;

[0042] Figure 6 This is a performance diagram of the five-time adsorption-desorption cycle of Co-Li / Al-LDH in Example 4 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0044] Unless otherwise specified, the raw materials and reagents used in the specific embodiments of the present invention are all commercially available.

[0045] The lithium adsorption capacity of the adsorbent in the following specific examples was tested in the following manner:

[0046] De-lithiation of the lithium adsorbent: the prepared adsorbent is loaded into an adsorption column, and deionized water is pumped into the adsorption column by a peristaltic pump, and the water is replaced every 2 hours for 2 days to desorb lithium from the lithium adsorbent;

[0047] Take 1.5g of lithium desorbed adsorbent and put it into 50ml of Li + In a solution with a concentration of 500 mg / L; put the lithium solution containing the adsorbent into a sealed plastic bottle, set the shaking speed to 200 rpm, and control the temperature between 25-45°C; after reaching adsorption equilibrium, take the supernatant to the scale and use ICP-OES to measure the concentration. Calculate the adsorption capacity based on the concentration difference before and after adsorption.

[0048] Example 1

[0049] This embodiment provides a Zn and F co-doped lithium adsorbent and its synthesis method and adsorption application, which specifically includes the following steps:

[0050] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, ZnCl2·6H2O (0.3 g), LiF (0.022 g) and 150 ml of deionized water. The temperature was controlled at 45°C and stirred continuously for 8 h to obtain a F and Zn doped adsorbent, which was recorded as F / Zn-Li / Al-LDHs.

[0051] This embodiment also includes the step of granulating the F / Zn-Li / Al-LDHs material prepared above, including: adding the F / Zn-Li / Al-LDHs powder (10 g) prepared above to a uniform mixed solution of PVC (0.4 g), PAN (1.6 g) and DMF (20 ml) at room temperature, and adding 0.2 g of ethylenediamine to obtain a uniformly dispersed slurry; then slowly injecting the mixed slurry into deionized water with a 1 ml syringe to solidify it, to obtain a granulated F / Zn-Li / Al-LDHs adsorbent.

[0052] The above-mentioned granulated F / Zn-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were carried out. The test results are shown in Table 1.

[0053] Example 2

[0054] This embodiment provides a S and Cu co-doped lithium adsorbent and its synthesis method and adsorption application, which specifically include:

[0055] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3.6H2O (10 g) at pH 10, CuCl2·2H2O (0.17 g), Al2S3 (0.052 g) and 150 ml of deionized water. The temperature was controlled at 60°C and stirred continuously for 7 h to obtain a S and Cu doped adsorbent, which was recorded as S / Cu-Li / Al-LDHs.

[0056] The obtained S / Cu-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated adsorbent.

[0057] The above-mentioned granulated S / Cu-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were carried out. The test results are shown in Table 1.

[0058] Example 3

[0059] This embodiment provides a Co and F co-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0060] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, CoCl2·6H2O (0.4 g), LiF (0.01 g) and 150 ml of deionized water. The temperature was controlled at 45°C and stirred continuously for 8 h to obtain a F and Co doped adsorbent, which was recorded as F / Co-Li / Al-LDHs.

[0061] The obtained F / Co-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated F / Co-Li / Al-LDHs adsorbent.

[0062] The above-mentioned granulated F / Co-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were carried out. The test results are shown in Table 1.

[0063] Example 4

[0064] This embodiment provides a transition metal Co-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0065] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, CoCl2·6H2O (0.49 g) and 150 ml of deionized water, the temperature was controlled at 45°C, and stirring was continued for 8 h to obtain a Co-doped adsorbent, which was recorded as Co-Li / Al-LDHs.

[0066] The obtained Co-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Co-Li / Al-LDHs adsorbent. The granulated Co-Li / Al-LDHs adsorbent was delithiated and then subjected to a lithium adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0067] Example 5

[0068] This embodiment provides a transition metal Mn-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0069] LiCl (10.59 g), AlCl3·6H2O (20.12 g), urea (6.81 g) (Li / Al / urea / molar ratio = 3:1:0.74), dopant MnCl2·6H2O (0.524 g) and 75 ml of deionized water were mixed to form a solution; the above solution was charged into a hydrothermal kettle, the temperature was set to 130°C, and the reaction was carried out for 8 hours; after the reaction was completed, the reactor was cooled, the reactants were washed and filtered, and then dried at 60°C to obtain a Mn-doped aluminum-based lithium adsorbent, recorded as Mn-Li / Al-LDHs.

[0070] The obtained Mn-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Mn-Li / Al-LDHs adsorbent.

[0071] The above-mentioned granulated Mn-Li / Al-LDHs adsorbent was delithiated, and then subjected to a lithium adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0072] Example 6

[0073] This embodiment provides a transition metal Zr-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0074] LiCl (10.59 g), AlCl3·6H2O (20.12 g), urea (6.81 g) (Li / Al / urea / molar ratio = 3:1:0.74), dopant ZrCl2·6H2O (0.971 g) and 75 ml of deionized water were mixed to form a solution; the above solution was charged into a hydrothermal kettle, the temperature was set to 130°C, and the reaction was carried out for 8 hours; after the reaction was completed, the reactor was cooled, the reactants were washed and filtered, and then dried at 60°C to obtain a Zr-doped aluminum-based lithium adsorbent, recorded as Zr-Li / Al-LDHs.

[0075] The obtained Zr-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Zr-Li / Al-LDHs adsorbent.

[0076] The granulated Zr-Li / Al-LDHs adsorbent was delithiated and then subjected to a lithium adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0077] Example 7

[0078] This embodiment provides a transition metal Zn-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0079] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, ZnCl2·6H2O (0.501 g) and 150 ml of deionized water, the temperature was controlled at 45°C, and stirring was continued for 8 h to obtain a Zn-doped adsorbent, recorded as Zn-Li / Al-LDHs.

[0080] The obtained Zn-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Zn-Li / Al-LDHs adsorbent. The granulated Zn-Li / Al-LDHs adsorbent was delithiated and then subjected to a lithium adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0081] Example 8

[0082] This embodiment provides a transition metal Ni-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0083] LiCl (10.59 g), AlCl3·6H2O (20.12 g), urea (6.81 g) (Li / Al / urea / molar ratio = 3:1:0.74), dopant NiCl2·6H2O (0.54 g) and 75 ml of deionized water were mixed to form a solution; the above solution was charged into a hydrothermal kettle, the temperature was set to 130°C, and the reaction was carried out for 8 hours; after the reaction was completed, the reactor was cooled, the reactants were washed and filtered, and then dried at 60°C to obtain Ni-doped aluminum-based lithium adsorbent, recorded as Ni-Li / Al-LDHs.

[0084] The obtained Zn-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Ni-Li / Al-LDHs adsorbent.

[0085] The above-mentioned granulated Ni-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were performed. The test structure is shown in Table 1.

[0086] Example 9

[0087] This embodiment provides a transition metal Cu-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0088] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, CuCl2·2H2O (0.35 g) and 150 ml of deionized water, the temperature was controlled at 60°C, and stirring was continued for 7 h to obtain a Cu-doped adsorbent, which was recorded as Cu-Li / Al-LDHs.

[0089] The obtained Cu-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Cu-Li / Al-LDHs adsorbent. The granulated Cu-Li / Al-LDHs adsorbent was delithiated and then subjected to an adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0090] Example 10

[0091] This embodiment provides a halogen F-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically includes the following steps:

[0092] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, LiF (0.053 g) and 150 ml of deionized water, the temperature was controlled at 45°C, and stirring was continued for 8 h to obtain a F-doped adsorbent, which was recorded as F-Li / Al-LDHs.

[0093] The obtained F-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated F-Li / Al-LDHs adsorbent. The granulated F-Li / Al-LDHs adsorbent was delithiated and then subjected to an adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0094] Embodiment 11

[0095] The present invention provides an S-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically comprises the following steps:

[0096] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, Al2S3 (0.103 g) and 100 ml of deionized water, the temperature was controlled at 40°C, and stirring was continued for 6 h to obtain an S-doped adsorbent, which was recorded as S-Li / Al-LDHs.

[0097] The obtained S-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated S-Li / Al-LDHs adsorbent.

[0098] The above-mentioned granulated S-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were carried out. The test structure is shown in Table 1.

[0099] Example 12

[0100] The present invention provides a P-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically comprises the following steps:

[0101] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, Na3PO4 (0.326 g) and 100 ml of deionized water, the temperature was controlled at 40°C, and stirring was continued for 6 h to obtain a S-doped adsorbent, which was recorded as P-Li / Al-LDHs.

[0102] The obtained P-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated P-Li / Al-LDHs adsorbent.

[0103] The above-mentioned granulated P-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were carried out. The test structure is shown in Table 1.

[0104] Embodiment 13

[0105] The present invention provides a Se-doped lithium adsorbent and a synthesis method and adsorption application thereof, which specifically comprises the following steps:

[0106] LiCl·H2O (3 g) was dropped into a mixed solution of AlCl3·6H2O (10 g) at pH 10, Na2SeO3 (0.346 g) and 100 ml of deionized water, the temperature was controlled at 40°C, and stirring was continued for 6 h to obtain a Se-doped adsorbent, which was recorded as Se-Li / Al-LDHs.

[0107] The obtained Se-Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Se-Li / Al-LDHs adsorbent.

[0108] The above-mentioned granulated Se-Li / Al-LDHs adsorbent was delithiated, and then the adsorption capacity test and Al dissolution test were carried out. The test structure is shown in Table 1.

[0109] Comparative Example 1

[0110] This comparative example provides a lithium adsorbent without doping, comprising the following steps:

[0111] LiCl (10.59 g), AlCl3·6H2O (20.12 g), urea (6.81 g) (Li / Al / urea / molar ratio = 3:1:0.74) were mixed with 75 ml of deionized water to form a solution; the solution was charged into a hydrothermal kettle, the temperature was set at 130°C, and the reaction was carried out for 8 hours; after the reaction was completed, the reactor was cooled, the reactants were washed and filtered, and then dried at 60°C to obtain an undoped aluminum-based lithium adsorbent recorded as LiAl-LDHs.

[0112] Li / Al-LDHs was granulated in the same manner as in Example 1 to obtain a granulated Li / Al-LDHs adsorbent. The granulated LiAl-LDHs adsorbent was delithiated and then subjected to an adsorption capacity test and an Al dissolution test. The test structure is shown in Table 1.

[0113] Figure 1 Electron micrograph of Co-Li / Al-LDHs prepared in Example 4 of the present invention. Figure 2It is the XRD diagram of the lithium adsorbent prepared in Examples 4-8 and Comparative Example 1 of the present invention. Figure 3 It is a partial enlarged view of the XRD of the lithium adsorbent prepared in Examples 4-8 and Comparative Example 1 of the present invention. Figure 4 It is the infrared spectra of the lithium adsorbents prepared in Examples 4-8 and Comparative Example 1 of the present invention. Figure 5 It is the Raman spectrum of Co-Li / Al-LDH of Example 4 of the present invention. Figure 6 This is a performance diagram of the five-time adsorption-desorption cycle of Co-Li / Al-LDH in Example 4 of the present invention.

[0114] Table 1 Composition and adsorption performance of lithium adsorbents in the embodiments of the present invention and comparative examples

[0115]

[0116]

[0117] Embodiment 14

[0118] Example 14 is substantially the same as Example 3, except that the granulation method is:

[0119] At room temperature, the F / Co-Li / Al-LDHs powder (10 g) prepared above was added to a uniformly mixed solution of PVC (2.4 g), PAN (0.6 g) and N-methylpyrrolidone (20 ml), and 0.0065 g of a silane coupling agent (3-(2,3-epoxypropoxy)propyltrimethoxysilane) was added to obtain a uniformly dispersed slurry; then the mixed slurry was slowly injected into deionized water with a 1 ml syringe to solidify to obtain a granulated F / Co-Li / Al-LDHs adsorbent.

[0120] Embodiment 15

[0121] Example 15 is substantially the same as Example 1, except that the granulation method is:

[0122] At room temperature, the F / Co-Li / Al-LDHs powder (10 g) prepared above was added to a uniformly mixed solution of PVC (1.25 g), PAN (1.25 g) and N-methylpyrrolidone (20 ml), and 0.2 g of polyethylene glycol diacrylate was added to obtain a uniformly dispersed slurry; then the mixed slurry was slowly injected into deionized water with a 1 ml syringe to solidify, thereby obtaining a granulated F / Co-Li / Al-LDHs adsorbent.

[0123] Comparative Example 2

[0124] The difference between Comparative Example 2 and Example 3 is that no cross-linking agent ethylenediamine is added during the granulation process, and the rest is the same as Example 3.

[0125] Comparative Example 3

[0126] The difference between Comparative Example 3 and Example 3 is that PAN is not added during the granulation process, and only 2 g of PVC is added. The rest is the same as Example 3.

[0127] Comparative Example 4

[0128] The difference between Comparative Example 4 and Example 3 is that no PVC is added during the granulation process, and only 2 g of PAN is added. The rest is the same as Example 3.

[0129] The adsorption performance and Al dissolution loss of the adsorption materials of Examples 1-3, Examples 14, 15, and Comparative Examples 2-4 before and after granulation were tested. The test results are shown in Table 2.

[0130] Table 2 Adsorption capacity and Al dissolution loss of adsorption materials before and after granulation in relevant embodiments and comparative examples

[0131]

[0132] In addition, the present invention also tested the application of the lithium adsorbents in the above embodiments in lithium extraction from salt lake brine, and all of them showed good lithium adsorption effects; in particular, the adsorbent granulated by the method provided by the present invention showed lower Al dissolution loss under long-term use conditions, indicating that the lithium adsorbent provided by the present invention has certain application prospects in lithium extraction from seawater and brine.

[0133] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0134] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0135] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A doped aluminum-based lithium adsorption material, characterized in that: The doped aluminum-based lithium adsorption material includes LiAl-LDHs and a doping element, wherein the doping element includes a transition metal element and / or a non-metal element, wherein the transition metal element includes one or more of Co, Mn, Zr, Zn, Cu, and Ni, and the non-metal element includes one or more of F, P, S, and Se; The molar ratio of Li to Al in the doped aluminum-based lithium adsorption material is 0.5-5:1, and the molar concentration of the doping element is 0.1-10% of the molar concentration of the Al.

2. The doped aluminum-based lithium adsorption material according to claim 1, characterized in that: The doped aluminum-based adsorption material includes a transition metal element and a non-metal element, wherein the transition metal element includes Co and the non-metal element includes F; or, the transition metal element includes Cu and the non-metal element includes S; or, the transition metal element includes Zn and the non-metal element includes F; And / or, the doped aluminum-based adsorption material includes transition metal elements and non-metal elements, and the molar ratio of the transition metal elements and the non-metal elements is 0.01-5:0.01-5.

3. A method for preparing a doped aluminum-based lithium adsorption material, characterized in that: include: A mixed reaction system containing a lithium source, an aluminum source, urea, a doping element precursor and a solvent is subjected to a hydrothermal reaction at a temperature of 100-180° C. for 2-12 hours to obtain a doped aluminum-based lithium adsorption material; Alternatively, providing a mixed solution containing an aluminum source, a doping element precursor and a solvent, and adjusting the pH value of the mixed solution to 8-10; Adding lithium sources to the mixed solution in batches to obtain a mixed reaction system, and maintaining stirring at a temperature of 20-80° C. for 2-8 hours to obtain a doped aluminum-based lithium adsorption material; Among them, the doping element precursor is used to provide transition metal elements and / or non-metal elements, the transition metal elements include one or more of Co, Mn, Zr, Zn, Cu, and Ni, and the non-metal elements include one or more of F, P, S, and Se.

4. The preparation method according to claim 3, characterized in that: The amounts of lithium source, aluminum source and doping element precursor in the mixed reaction system satisfy: the molar ratio of Li to Al contained in the doped aluminum-based lithium adsorption material is 0.5-5:1, and the molar concentration of the doping element contained is 0.1-10% of the molar concentration of Al contained; And / or, the doping element precursor can provide a transition metal element and a non-metal element precursor, and the amount of the doping element precursor is such that the molar ratio of the transition metal element to the non-metal element in the prepared doped aluminum-based lithium adsorption material is 0.01-5:0.01-5; And / or, the doping element precursor includes a Co precursor and a F precursor; or, the doping element precursor includes a Cu precursor and a S precursor; or, the doping element precursor includes a Zn precursor and a F precursor; And / or, the molar concentration of urea in the mixed reaction system is 0.5-2 times the molar concentration of aluminum.

5. The preparation method according to claim 3, characterized in that: The lithium source includes one or more of lithium chloride, sulfate or nitrate; And / or, the aluminum source includes one or more of aluminum chloride, sulfate or nitrate; And / or, the precursor providing the transition metal element includes one or more of chlorides, nitrates, sulfates or carbonates of the transition metal element.

6. The preparation method according to claim 3, characterized in that: The precursors providing F include one or more of LiF, NaF, and KF; the precursors providing P include one or more of phosphoric acid, Na3PO4, K3PO4, Ca3(PO4)2, Na4P2O7, and NaH2PO2; the precursors providing S include soluble sulfides and / or soluble sulfates, and the soluble sulfides include Al2S3; the precursors providing Se include one or more of Na2SeO3, H2SeO3, K2SeO3, H2SeO4, K2SeO4, and Na2SeO4.

7. A doped aluminum-based lithium adsorption material, characterized in that: The method is prepared by the method described in any one of claims 3 to 6.

8. A lithium adsorbent, characterized in that: The raw materials of the lithium adsorbent include the doped aluminum-based lithium adsorbent material according to claim 1, 2 or 7, polyvinyl chloride, polyacrylonitrile and a crosslinking agent; the ratio of the mass of the doped aluminum-based lithium adsorbent material to the total mass of polyvinyl chloride and polyacrylonitrile is 3:1-5:1, the mass ratio of polyvinyl chloride to polyacrylonitrile is 0.2:0.8-0.8:0.2, and the concentration of the crosslinking agent is 0.05-10wt% of the total mass of the doped aluminum-based lithium adsorbent material, polyvinyl chloride and polyacrylonitrile; Preferably, the cross-linking agent includes one or a combination of ethylenediamine, a silane coupling agent, and polyethylene glycol diacrylate.

9. The method for preparing the lithium adsorbent according to claim 8, characterized in that: include: Providing the doped aluminum-based lithium adsorption material according to claim 1, 2 or 7; At least the doped aluminum-based lithium adsorbent material, polyvinyl chloride, polyacrylonitrile and a crosslinking agent are uniformly dispersed in a polar aprotic solvent to obtain a mixture; injecting the mixture into water to solidify the mixture in the water, and performing solid-liquid separation to obtain a solidified product, which is a granulated lithium adsorbent; Preferably, the polar aprotic solvent comprises dimethylformamide and / or N-methylpyrrolidone.

10. Use of the doped aluminum-based lithium adsorption material according to claim 1, 2 or 7 or the lithium adsorbent according to claim 8 in extracting lithium from brine or seawater.